VARIASI INTRASPESIES Monascus purpureus DALAM BERBAGAI SAMPEL ANGKAK DARI JAWA TIMUR - Nandang Suharna (BERITA BIOLOGI, 2009)
Study was carried out to know intraspecific variation within Monascus purpureus in Chinese red rice (angkak) collected from a number of cities in East Java, covering isolation, characterization and identification of Monascus based on cultural and microscopic characters.Results showed that cultural and microscopic observation on 19 representative isolates of Monascus which each isolate was observed from 19 sample of angkak showed variations among those isolates.Those characters were rate of growth, pigmentation,crystalline hyphae, spore size and cleistothecium diameter.These results indicated that there are intraspecies variaty on M.purpureus used in angkak production. Moreover, cultural and morpholological characters such as colony diameter and askomata seemingly can not be used as taxonomic characters.